Analisis Pengendalian Kualitas Mutu Udang Black Pink (Metapenaeus Monoceros) dengan Metode Statistical Quality Control di PT. Dachan Mustika Aurora Tarakan Utara - Nurhasanah Nurhasanah; Mariam Mariam; Andi Rusdi Walinono (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2024)
Black pink shrimp is a type of small shrimp with light brown characteristics to resemble the color of small milk coffee, which is 2-4 cm in length. The purpose of this study was to determine the Quality Control of Black Pink Shrimp (Metapenaeus monoceros) with the Statistical Quality Control method. The data analysis used is quantitative analysis. The data sources used are primary and secondary data. The data analysis technique used is control map analysis (P Chart). The data collection methods used are observation, and literature study. The sample used was black pink shrimp. The results showed On the control map p it is known that the value of the upper control limit / Upper Control Limit (UCL) is 1.08, the average P is 0.659, and the value of the lower control limit / Lower Control Limit (LCL) is 0.21. UCL and LCL values are used as guidelines to define a process within control limits. Based on the graph, it can be seen that the production process of frozen shrimp products is still not under control because there are two samples that are beyond the upper control limit, namely in the 8th week and 13th week samples. The control carried out if there is a decrease in quality in the product, namely, telson butts and clubs of two segments are transferred to broken products and QC ensures that the SOPs applied run properly and correctly.